Precise sampling of soil Pre-requisite for evaluation of soil health - Isha; Gautam, Poonam (Indian Farming, 2024)
Soil health is essential for sustaining crop productivity and ecological balance in agricultural ecosystems. But decline in soil health, caused by both natural and anthropogenic factors, poses global challenges, especially in developing nations. Maintaining soil health therefore becomes necessary and reliable soil test results can accurately depict soil health status while reducing the cultivation costs. However, achieving accuracy requires collection of representative soil sample and following precise soil sampling techniques, including field surveys, collection methods based on crop type along with appropriate mixing, quartering, and labelling of soil samples. Adherence to the sampling protocols can sustain soil health, increase crop yield and facilitate precise fertilization recommendations.